1995
DOI: 10.1007/bf00001819
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic costs of viviparity in yellowtail rockfish,Sebastes flavidus

Abstract: We estimated the energy utilized by developing embryos and larvae of yellowtail rockfish, Sebastesflavidus, by determining the routine metabolic rate of adult females throughout gestation and subtracting the mean metabolic rate of non-gestating fish. The pattern of maternal oxygen consumption during gestation was such that metabolic demands did not become significantly elevated until intra-ovarian embryos had hatched and larvae were being incubated (i.e. 24-28 d post-fertilization).Metabolic rates of females i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A number of studies have reported elevated metabolic rate (Webb and Brett, 1972;Boehlert et al, 1991;Hopkins et al, 1995;Timmerman and Chapman, 2003;Skov et al, 2010) and diminished swimming performance (Plaut, 2002;Ghalambor et al, 2004;Belk and Tuckfield, 2010) in pregnant live-bearing fish. The studies differ from the present study in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported elevated metabolic rate (Webb and Brett, 1972;Boehlert et al, 1991;Hopkins et al, 1995;Timmerman and Chapman, 2003;Skov et al, 2010) and diminished swimming performance (Plaut, 2002;Ghalambor et al, 2004;Belk and Tuckfield, 2010) in pregnant live-bearing fish. The studies differ from the present study in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-exercise M O 2 at 2BLs −1 is indicated using a solid line (dashed lines are 95% CL). Locomotor cost and maximal performance Hopkins et al, 1995;Skov et al, 2010). We were unable to make repeated measurements on individual fish because of the destructive nature of measuring RA, and our samples included no reproductively inactive fish (all wet RA ≥4.93%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated whether this hypothesis can contribute to explaining the maintenance of a melanophore pattern polymorphism in X. helleri by examining whether spotted and nonspotted morphs of X. helleri differ in routine metabolic rate. We tested both adult males and juveniles (we did not measure the metabolic rate of females because it may vary with reproductive state and this could be a confounding factor; Hopkins et al 1995). We chose the green swordtail X. helleri as our study system because it belongs to a different clade of Xiphophorus and its pattern polymorphism is phenotypically but not necessarily genetically different (Kallman and Atz 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Hopkins et al (1995) used oxygen consumption rates to determine metabolic rates of yellowtail rockfish Sebastes flavidus. They found that females incubating larvae had an 82 to 101% higher metabolic rate than spent females and males (Hopkins et al 1995). This study also calculated the maternal nutrient contribution to the embryo.…”
Section: Discussionmentioning
confidence: 99%